Fibroblast growth factor 23 is an independent marker of COPD and is associated with impairment of pulmonary function and diffusing capacity. (June 2021) - Kraen, M.; Frantz, S.; Nihlén, U.; Engström, G.; Löfdahl, C.G.; Wollmer, P.; Dencker, M.
Abstract: Fibroblast growth factor 23 (FGF23) is a phosphaturic hormone that in recent years has been reported to have significant effects on numerous tissues. Chronic obstructive pulmonary disease (COPD) is associated with hypophosphatemia but the evidence for elevated plasma levels of FGF23 in COPD subjects is ambiguous. Recently, FGF23 has even been shown to be involved in the inflammatory pathways activated in COPD, so FGF23 could be a novel biomarker for COPD and impairment of pulmonary function. The purpose was thus to explore the association of FGF23 with COPD and measures of pulmonary function. This was a cross sectional study of 450 subjects who underwent spirometry, body plethysmography, determination of diffusing capacity (DL, CO) and biomarker analysis of FGF23, interleukin (IL)-1 receptor antagonist, IL-6 and IL-8. Forty-four participants were excluded due to missing data or renal impairment (eGFR <45 mL/min/m2). Spirometry identified 123 subjects with COPD. FGF23 levels were elevated in COPD subjects compared to non COPD subjects, and this remained significant after adjustment for age, sex and smoking habits (OR = 1.6, p = 0.02). Linear regression showed significant relationships between FGF23 and FEV1 (β = −0.15, p = 0.003), RV/TLC (β = 0.09, p = 0.05) and DL, CO (β = −0.24, p < 0.001). In conclusion we found that plasma levels of FGF23 are elevated in COPD subjects even when adjusting for traditional risk factors. Furthermore, FGF23 is associated with impairment in lung function as measured by FEV1 and DL, CO. Further studies are needed to establish whether FGF23 could serve as a novel biomarker of COPD and emphysema development. Highlights: FGF23 levels are elevated in COPD subjects. FGF23 is associated with impairment in lung function. FGF23 could serve as a novel biomarker of COPD and emphysema.